A study conversion to be mining cement in Maruni protected forest Manokwari Regency - Mahmud, Mahmud; Budirianto, Heru Joko; Wahyudi, Wahyudi; Kusumandari, Ambar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Protected forests play an important role in supporting human life, protecting land and water and preventing the dangers of flooding and landslides, but a lot of conversions have taken place today. Research-based on techniques for observation, interviews, and case studies. Measurement of respondents’ perceptions and attitudes is carried out using instruments in the form of questionnaires that refer to the Likert scale. Data analysis was performed descriptively to describe the level of perception, attitude with simple non parametric linear regression. Maruni protected forest has the potential of limestone with 11 mineral elements, 5 of which are the largest Ca (93.62%), Si (2.45%), Mg (1.58%), Al (0.97%) ) and K (0.47%). This forest allows conversion area, from an area of ​​969.84 ha with limestone potential of only 250 ha (25.78%), another 719.84 ha (74.22%) can still be designated as a protected forest. The public perception of conversion to cement mining was 59.03% negative, 14.83% neutral and 26.12% positive. While the attitudes of the community 43.1% accept, 38.94% neutral and 47.92% reject the conversion to become cement mining. The community hopes that there will be economic improvement, community empowerment and employment, especially affected communities. Keywords: Conversion, cement mining, Maruni protected forest/HLM, perception, attitude